ANALISIS PENGARUH FUNDAMENTAL PERUSAHAAN TERHADAP RETURN SAHAM PADA PERUSAHAAN-PERUSAHAAN PROPERTI - Slamet Herutono (Akademi Akuntansi YKPN Yogyakarta, 2010)
Fundamental factor is one of factor used by investors to make investment decission in the capital market. This study investigate the impact of fundamental factor of company on return stock. The data used in this research are the data of financial statement and stock price in the Indonesian Capital Market Directory (ICMD) 2001-2006. The sample comprised 126 pooled companies from property industry listed on the Bursa Efek Indonesia (BEI) for the period of 2001 - 2006. The variables are current ratio, debt to equity ratio, return on equity, price earning ratio, and book to market ratio. The result proved that current ratio, debt to equity ratio, return on equity, price earning ratio, and book to market ratio simultaneously have significant effect on return of stock. But debt to equity ratio and return on equity individually have significant effect on return of stock. Overall of independent variables could explain about 20,2 percent variation return of stock and the rest explained by other variables about 79,8 percent. It means that the fundamental factor of company is not only factor that infuenced return of stock in the Bursa Efek Indonesia (BEI).Keywords: fundamental factor, current ratio, debt to equity ratio, return on equity, price earning ratio, book to market ratio, return of stock.